Q. 1 B5.0( 2 Votes )

# Solve the followi

x2 + (1 – 2i)x – 2i = 0

Given x2 + (1 – 2i)x – 2i = 0

x2 + x – 2ix – 2i = 0

x(x + 1) – 2i(x + 1) = 0

(x + 1)(x – 2i) = 0

x + 1 = 0 or x – 2i = 0

x = –1 or 2i

Thus, the roots of the given equation are –1 and 2i.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

–x2 + RD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve the fRD Sharma - Mathematics

Solve:
<
RD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics